Facile synthesis of poly(BODIPY)s via solid state polymerization and application in temperature sensor. (15th February 2022) - He, Guohang; Lu, Qingyi; Xu, Feng; Zhang, Dongkui; Li, Ying; Xia, Jiangbin
Abstract: Several 3, 5-dibromo substituted BODIPY (4, 4′-Difluoro-4-bora-3a, 4a-diaza-s-indacene) derivatives were rationally designed and investigated as potential candidates to perform solid state polymerization (SSP). Compared with the traditional systems of thiophene and diacetylene families, which were successfully applied in SSP, SSP has been expanded to the BODIPY system in this article. In addition, crystallographic data of BODIPY derivative was derived to analyze the reasonable path of SSP, which could further explore the mechanism of SSP. Furthermore, the relationship between fluorescence intensity of BODIPY after SSP and temperature was established, which could apply this material in temperature fluorescence sensor with outstanding relative sensitivity (Sr ) of 0.898% K −1 . Our work has been proved to pave the way to explore more conjugated systems by using SSP method and enrich SSP database systematically. Graphical abstract: Several 3, 5-dibromo substituted BODIPY (4, 4′-Difluoro-4-bora-3a, 4a-diaza-s-indacene) derivatives were rationally designed and investigated as potential candidates to perform solid state polymerization (SSP). In addition, crystallographic data of BODIPY derivative was derived to analyze the reasonable path of SSP, which could further explore the mechanism of SSP. Furthermore, the relationship between fluorescence intensity of BODIPY after SSP and temperature was established, which could apply this material in temperature fluorescence sensor with outstanding relative sensitivity (Sr ) of 0.898% K −1 . Image 1 Highlights: ∙ Dibromo substituted BODIPY derivatives were investigated to perform solid state polymerization. ∙Crystallographic of monomer was derived to analyze the reasonable path of SSP. ∙The monomer was explored as temperature fluorescence sensor with outstanding relative sensitivity (Sr ) of 0.898% K −1 .